2021
DOI: 10.1177/0031721721998152
|View full text |Cite
|
Sign up to set email alerts
|

Mixed reality simulations for social-emotional learning

Abstract: Although social-emotional learning is associated with long-term success in school and careers, it is often a missing link in U.S. public education. The COVID-19 pandemic has intensified the need for social-emotional supports for children. In this time of crisis, educators have also sought new ways to make connections and reimagined how students might actively learn with each other. Kristin Murphy, Amy Cook, & Lindsay Fallon discuss what they have learned about using mixed reality simulations to facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to García Carbonell et al ( 2012), simulation does not dissect knowledge and communication skills, but rather fosters professional competence through a global cognitive process, which optimises results and justifies the full integration of simulation into curriculum design. Authors like McCrary and Mazur (2010) and Murphy and Cook (2020) have suggested that incorporating simulations into the classroom can promote dialogic learning. Dialogue is central to classroom simulations.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…According to García Carbonell et al ( 2012), simulation does not dissect knowledge and communication skills, but rather fosters professional competence through a global cognitive process, which optimises results and justifies the full integration of simulation into curriculum design. Authors like McCrary and Mazur (2010) and Murphy and Cook (2020) have suggested that incorporating simulations into the classroom can promote dialogic learning. Dialogue is central to classroom simulations.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…MRS topics include classroom management (Larson et al, 2020), non-verbal immediacy behaviors (Rosati- Peterson et al, 2021), collaborative skills in inclusive settings (Driver et al, 2018), differential reinforcement of incompatible behaviors (Judge et al, 2013), and specific praise and error correction (Dawson & Lignugaris/ Kraft, 2017). Yet, some researchers are concerned about the amount of time required to learn a skill in the simulator (Driver et al, 2018;Murphy et al, 2021). Others have expressed concerns regarding the costs associated with MRS (Walters et al, 2021).…”
Section: Mixed-reality Simulationmentioning
confidence: 99%
“…MRS is a promising, emergent technology in PST education. In addition, there was an influx of MRS due to COVID-19-related school site restrictions for PSTs (Murphy et al, 2021). The purpose of this article is to highlight how one university integrated MRS experiences across two PST special education courses during school site restrictions while studying the effectiveness of MRS.…”
mentioning
confidence: 99%
“…Results of quantitative research conducted in the U.S. showed that teacher beliefs about the importance of SEL were influenced by a student's grade level, and that it was seen as somewhat less important for older cohorts (Bridgeland et al, 2013). SEL has also been shown to be particularly important during the COVID-19 pandemic in helping students navigate challenging times (Murphy et al, 2021). During the pandemic, many children and youth reported symptoms of inattention, irritability, and fearfulness (Singh et al, 2020).…”
Section: Importance Of Selmentioning
confidence: 99%